The study on operational and safety of heavy machinery in construction site / Adrian Charles Alidin - Alidin, Adrian Charles (Faculty of Architecture, Planning and Surveying, UiTM Shah Alam, 2010)
In the fields of architecture and civil engineering, construction is a process that consists of the building or assembling of infrastructure. Far from being a single activity, large scale construction is a feat of multitasking. Normally the job is managed by the project manager and supervised by the construction manager, design engineer, construction engineer or project architect and also all the workers in site and the equipment and also the machine. In construction site, the relationship between the human and machine is very important. The heavy machinery always used in non-heavy and heavy construction. The example of heavy machinery is such as tower crane, mobile crane, excavator, backhoe, lorry, dozer and many more. The heavy machinery job is doing earthwork, transport material and so on. Heavy machinery is handled by human and called operator. A good operator will give good operational to heavy machinery. A good operational of heavy machinery will give safety to construction site. This study is on the operational and safety of heavy machinery in construction site. The study will be focus on the heavy machinery and its operator, where to know how the operator handling the machinery, to know the maintenance of the heavy machinery and also the safety of heavy machinery. An operational knowledge of the heavy machinery is very important. The operational heavy machinery is always close to the safety in site. To determine the heavy machinery operational and safety, site survey carried out to several construction which relevant to research or study.